PERLINDUNGAN HUKUM TERHADAP AWAK KAPAL PERIKANAN INDONESIA DARI KEJAHATAN TRANSNASIONAL - Esther Lina Tumanggor (2022)
The mobility of workers across the territorial boundaries of state jurisdiction is carried out by the international community, including the state of Indonesia. Foreign exchange receipts and inflows of funds from remittances delegated by Indonesian fishing vessel crews are felt by Indonesia especially in Indonesia's balance of payments. Unfortunately, the mobility of Indonesian fishing vessel crews who do work outside the jurisdiction of Indonesia, creates the stimulation of transnational crimes of human trafficking, modern slavery over the labour, violence, and other human rights violations, as stated in the preamble to Law No. 18 of 2017. The purpose of this study is to determine the factual problems in the field that have a correlation with the mechanism for the recruitment and placement of Indonesian fishing vessel crews who will work abroad, and how the Indonesian government takes steps to protect Indonesian fishing vessel crews before work, during work, and after work that is relevant to the problem raised. The author's research is a qualitative research with a normative jurisprudential method, so that the selected sources come from library data, primary, secondary, and tertiary legal sources material. The results of the research by the authors of the transnational crime of human trafficking start from the mechanism for the recruitment and placement of Indonesian fishing vessel crews before and during work. Protection for Indonesian fishing vessel crews delegated by the Indonesia Government is carried out in synergy between Government agencies, including the diplomacy of Indonesian representatives from the Ministry of Foreign Affairs.